Nasolabial Flap Tunneled Under Mandible (NLFTUM) - An Alternative to Free Flap, in T3 Tongue Reconstruction - Riju, Dr. Jeyashanth; Thomas, Dr. Shaji; Mathew, Dr. Elizabeth; George, Dr. Nebu Abraham (International Journal of Innovative Research in Medical Science, 2018)
Introduction : Nasolabial flap tunneled under mandible(NLFTUM) is a good option for reconstruction of any T3 lesion in the oral cavity. It is oncologically safe and gives a better functional outcome compared to other locoregional flaps. When compared to free flap it is a cost effective and time saving procedure. Methods: We present a series of our results wherein NLFTUM was used in 9 patients who presented with biopsy proven carcinoma tongue, clinically T3 lesion which was away from the mandible. Wide excision of lesion was performed with neck dissection and NLFTUM reconstruction was used in all patients, preserving mandible. All these surgeries were performed in 2017 in a 5 months window period. A total of 9 flaps were harvested. Adjuvant radiotherapy was given when indicated. Results: Reconstruction was done in 9 patients in whom 7 were men and 2 women. Mean size of the surgical specimen for which reconstruction done was 5.3 +/- 0.6cm. 89% cases had defect which reached posterior 1/3rd tongue. Reconstruction was successful in 89% of the cases. Total flap necrosis occurred in 1 patient, 2 patient had minimal necrosis in the distal end of the flap, all were managed conservatively. Oral function and swallowing were satisfactory in all these patients. Cosmetic result was comparable to the normal nasolabial flap. There was no major complication associated with the procedure, none needed any major intervention. Conclusion: NLFTUM is reliable for reconstruction of lesion with defect which is as big as 6 cm in oral cavity, especially for tongue defects, even if it extends to posterior 1/3rd. We have used this in tongue defect because of its excellent functional outcome and there is no risk of added complications.